A convolution type characterization for Lp - multipliers for the Heisenberg group. Issue 2 (2007) - Radha Radha, R. R.; Vijayarajan Vijayarajan, A.K. A.K.
Abstract : It is well known that if m is an L p - multiplier for the Fourier transform on ℝ n ( 1 < p < ∞ ), then there exists a pseudomeasure σ such that T m f    = σ * f . A similar result is proved for the group Fourier transform on the Heisenberg group H n . Though this result is already known in generality for amenable groups, a simple proof is provided in this paper.